SOME FEATURES OF THE POWER SUPPLY OF RESIDENTIAL BUILDINGS DURING THE HEATING SEASON - S. N. Osipov; V. M. Pilipenko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2017)
A large proportion of consumption of different types of energy by the residential sector, especially in the heating period, makes the energy efficiency of buildings without considering the loss of fuel with a significant reduction in hourly load on the generators, especially at night, already insufficient for real energy savings. Therefore in Belarus, in order to attract the consumer, electricity tariff for heating at night hours (from 11 p.m. to 6.00 a.m.) is three times cheaper than at any other time. Significant increase of the electricity consumption of at night could be achieved by using heat accumulators for heating and hot water supply to the residential sector. Particularly effective are water accumulators of heat and accumulators of underfloor heating that enable to use a coolant with a temperature of 40 оC and to increase the useful supply of heat. The use of heat accumulators for daily heating, ventilation and hot water supply of buildings significantly reduces the cost of creating the infrastructure of the territory under construction by eliminating the necessity of running the distribution network of heat or gas supply. The use of the heat accumulators is necessary due to the increase of the time-weighted average outdoor temperature. The mentioned increase in the City of Minsk in the heating season is of about 0.1 °C per year in average, and as for the last 20 years, the increase has led to a reduction of the required heat load on the premises by about 10 %. Research and project work on choosing the most effective options for the arrangement and use the heat accumulators in buildings of the various functions ought to be fulfilled in order to make the application of heat accumulators successful. In this respect civil and power engineers as well as operators should work together so to determine the chronological, technical and economic conditions of charging and use of heat accumulators.